PEMILIHAN METODE MATERIAL REQUIREMENT PLANNING PADA PERENCANAAN KEBUTUHAN BAHAN BAKU PROSES PRODUKSI DOMPET (INVANTRI (Inovasi Dan Pengelolaan Industri), 2022)
Abstract The production process is the core of a manufacturing company's activities. Andi Jaya Group is a home industry engaged in the manufacture of wallets. Having the right amount and time to get raw materials aims to support the smooth production process and avoid shortages and excess of raw materials that can have an impact on costs incurred. The purpose of this study was to determine the amount of raw material each time production so that effectiveness can be achieved using the MRP method of Lot For Lot Technique and Economic Order Quantity and knowing the amount of production scheduling for each period and knowing the total cost of raw material inventory production using the MRP method. Forecasting is an estimate of the level of demand for product needs over the next several periods using the linear regression method, moving average (MA), exponential smoothing to find out the estimated product demand. Material requirements planning is a method to determine the production process planning and raw material requirements in each component and determine the lead time for orders. From the analysis of data management carried out by the forecasting method, 50912 units were selected for the next 12 periods. The need for raw materials according to the MRP method The lot for lot (LFL) technique is the raw material for butega, lavender and 0.3 mm mica because the raw materials are always available and the total price of the wallet product is Rp. 18. 600,000. while the raw materials that use the EOQ calculation are zippers and sewing thread because they often run out of stock/delays in raw materials and the total price of the product for 12 periods of the wallet is Rp. 176,280,359